PROFITABILITAS DAN SOLVABILITAS PADA FINANCIAL DISTRESS PERUSAHAAN TEKSTIL DAN GARMEN - Rudiyanto Rudiyanto; Rizkya Nuranisa (The Asia Pacific Journal Of Management Studies, 2021)
This study was conducted to know the effect of return on assets, return on equity, and debt ratio on financial distress in Textile and Garment's companies listed on the Indonesia Stock Exchange (BEI) for the 2013-2018 period both partially and simultaneously. The method used quantitative research and descriptive with purposive sampling. We used 66 data from 11 companies, then analyzed using logistic regression to conclude. It was concluded that the results of the coefficient of determination using Nagelkerke's R Square of 73.6%. The results of the hypothesis test of this study that is either partially or simultaneously return on assets, return on equity, and debt ratio influence and significantly to financial distress.